SKRINING FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN BEBERAPA FRAKSI DARI KULIT BATANG JARAK (Ricinus communis L.) - Wulan Agustina; Nurhamidah Nurhamidah; Dewi Handayani (ALOTROP, 2017)
[PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITY OF SOME FRACTIONS FROM BARK OF CASTOR (Ricinus communis L.)]. The Phytochemical screening was conducted to determine secondary metabolites found in the bark of castor (Ricinus communis L.).The test results of phytochemical screening that has been done presence of  phenolic, flavonoids, alkaloids, saponins, and terpenoids. Extraction is done by maceration using ethanol 96%. Tests performed on the fraction of the antioxidant activity of ethanol, ethyl acetate, n-hexane, and ascorbic acid as compared to using DPPH. The results of measuring the antioxidant activity using Uv-Vis Spectrophotometer IC50 values obtained succession namely fraction of ethanol, ethyl acetate, n-hexane, and ascorbic acid, 33,38, 24,38, 289, 05 and 12, 48 ppm. Fraction of ethanol and ethyl acetate has a very strong antioxidant activity due IC50<50 ppm while the n-hexane fraction very weak antioxidant activity. Phenolic and flavonoids the bark of castor that can be potentially as antioxidants